ASSESSMENT OF THE IMPACT OF CAPACITY-BUILDING TRAINING ON HEALTHCARE WORKERS AT POINTS OF ENTRY IN PAKISTAN - D.N. Noreen; F. Bashir; I. Naveed (International Journal of Infectious Diseases, 2023)
Intro: Meeting the International Health Regulations (IHR)(2005) obligations to prevent,detect,control and respond to all public health threats at Points of Entry (POE) is a universal challenge.Central Health Establishments (CHE)is the focal point of IHR 2005 implementation on the POEs across Pakistan.The core capacities at POEs require strengthening through adequate and updated training for the Healthcare workers(HCW).With this objective,CHE designed this study aimed to assess the impact of a two-day training on components of core capacities and public health emergency response at POEs. Methods: The content of the training program was conceived to improve knowledge,attitude, and practice(KAP) related to core capacities required at POE. A 20-point questionnaire was divided into four domains:screening protocols, infection prevention,and control knowledge to assess the KAP related to core capacities to respond to public health threats.The questionnaire comprised of four sections:demographic details, knowledge (30 items), attitude(12 items), and practice(12 items) with total scoring of 30,60, and 24 respectively.The pre-post knowledge assessment was done and an impact assessment survey was undertaken among the participants who completed six months post-training period.Data was analyzed using SPSS version 24.Paired-t-test was used to assess the effect of training on knowledge. Findings: A total of 653 HCWs were trained through 17 two-day pieces of training for six months (June 2021 till January 2022). The mean age of participants was 37.6± 6.3 with a median experience of 6 (IQR: 2–15).Mean improvement in knowledge score was found to be significant (p<0.001)with a mean knowledge score of 21.4±5.2 in pre-test and 26.2±4.5 in post-test out of 30.The impact assessment survey suggested a change in knowledge and practice of HCWs Conclusion: The two-day training programs helped the HCW at POEs to enhance their knowledge related to IHR 2005 core capacities.The study provided a roadmap to enhance IHR (2005) implementation in an effective,meaningful, and sustainable manner through health education among HCWs.